A cross Sectional Study on Factors Associated with Premenstrual Syndrome among Female Students in Medical Colleges of Mosul University - Mazin, Abdulrahman; Attia, Younes; Abd Ahmed, Atheer; Fathi, Karam Yaseen (Jurnal Berita Ilmu Keperawatan, 2025)
Premenstrual syndrome is a prevalent health issue, especially among female medical school students, affecting their academic and professional performance. The study aimed to assess the extent of PMS experienced by female medical school students and identify factors that can be associated with the severity of PMS symptoms. A descriptive, cross-sectional design utilizing a quantitative approach was adopted from October 8th, 2022, to March 30th, 2023. Simple random sampling was used to select a sample of 185 students from Mosul University Medical Colleges, with 51 students from the Nursing College, 44 from the Medicine College, 47 from the Pharmacy College, and 43 from the Dentistry College. Data were collected using a structured questionnaire and Premenstrual Syndrome Scale. The sample consisted of female students whose mean age was 22.6 ± 4 years and whose body mass index was 22.8 ± 4.4. Of the total sample, 97 participants (52.4%) reported not participating in physical activity. Furthermore, 79 students (42.7%) exhibited moderate symptoms of premenstrual syndrome (PMS), while 27.6% reported severe symptoms of PMS, assessed using the premenstrual scale. In conclusion, the study found a significant statistical difference between cycle duration, duration of menses, regularity of period, amount of bleeding, duration of premenstrual symptoms, and familial history of PMS concerning the severity of PMS symptoms; further studies could explore the potential role of dietary and lifestyle modifications in the management of PMS symptoms and develop effective interventions to address its impact on female students.